Prevalence and potential risk factors of chronic pruritus among community middle‐aged and older population in Beijing, China. (25th March 2022) - Ju, Y.; Pei, H.; Kang, N.; Zhang, Y.; Zhang, C.; Chen, G.; Xie, Z.; Wang, D.
Abstract: Background: Chronic pruritus is a common problem among older adults, with a significant impact on their quality of life. However, it is under‐studied epidemiologically, especially among Chinese older adults. Objective: The aim of this study was to identify the prevalence and explore the risk factors of chronic pruritus among the middle‐aged and older adults in Beijing, China. Methods: A total of 929 participants aged ≥35 years from six communities in Beijing, China, were interviewed. The survey collected the demographic characteristics, the experience of chronic pruritus (>6 weeks), chronic disease history, the level of physical activities and sleep quality. A population‐based case–control study was conducted, including 178 chronic pruritus cases and 697 controls. A multivariate logistic regression model was performed to explore the risk factors of chronic pruritus. Additionally, a random forest algorithm was used to rank the importance of potential risk factors and analyse the overall interpretation of risk factors. Results: The prevalence of chronic pruritus was 19.48% (181/929) among the Beijing middle‐aged and elderly population. The findings indicated that older adults aged 65 years old or above, male, with college or higher degree, alcohol drinking, hypertension, hyperlipidaemia, chronic lung disease, cardiovascular disease, digestive system disease and osteoarthritis/rheumatism, and middle or low sleep quality were associated with the increased risk of chronic pruritus respectively. Physical activity level (≥3000 Met) was associated with a decreased risk of chronic pruritus. The rank according to the most contribution of chronic pruritus risk was sleep quality, education, physical activity level, osteoarthritis/rheumatism, age and gender. Conclusion: Prevalence of chronic pruritus was high among the Chinese middle‐aged and elderly population. Age, gender, high education, alcohol drinking, hypertension, hyperlipidaemia, chronic lung disease, cardiovascular disease, digestive system disease, osteoarthritis /rheumatism and poor sleep quality may serve as risk factors of chronic pruritus. Moderate and high physical activity levels may serve as protective factors of chronic pruritus risk.